Analisis Kemampuan Literasi Matematika Siswa Daerah 3T pada Materi Lingkaran Ditinjau dari Kecemasan Matematika - Zacharias, Rensa; Moma, La; Lekitoo, John Nandito (Media Pendidikan Matematika, 2025)
This study aims to analyze the mathematical literacy skills of students in underdeveloped, frontier, and outermost (3T) areas, specifically Grade VIII students at SMP Negeri Tiakur, on the topic of circles, in relation to their level of mathematics anxiety. The main focus is to examine how mathematics anxiety affects students’ abilities to understand, represent, and solve contextual mathematics problems rooted in local culture. This research employs an exploratory method with a descriptive qualitative approach. The subjects consist of six students selected purposively based on categories of high, moderate, and low anxiety. Data were collected through an anxiety questionnaire, a PISA level 3 problem, and in-depth interviews. Data analysis included reduction, presentation, and conclusion drawing. The findings indicate that mathematics anxiety influences student performance in solving contextual problems. Students with high anxiety can still demonstrate reflective and procedural abilities if they possess strong conceptual understanding. Conversely, students with moderate or low anxiety may struggle when lacking reflective and conceptual skills. The study concludes that authentic context-based learning, such as ethnomathematics, and attention to students’ affective aspects are essential to enhance their mathematical literacy, particularly reflective thinking and problem-solving skills